Trinuclear copper cluster atomic-scale catalyst as well as preparation method and application thereof
Synthesis of atomic catalysts of three-core copper clusters through second-level pyrolysis printing technology solves the problem of poor controllability of catalyst synthesis and difficulty in generating multi-carbon products, and achieves the efficient and highly selective CO2 conversion effect into ethanol, which has great Industrial application potential.
Patent Information
- Application Number
- CN202411662836.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the existing electrocatalytic carbon dioxide reduction technology, catalyst synthesis is poor, and agglomeration is prone to generate unfavorable nanoparticles, and it is difficult to efficiently generate polycarbon products with high economic value.
The three-core copper cluster atomic catalyst is synthesized by the second-level pyrolysis printing technology, and copper ions and nitrogen atoms are dispersed through graphene-based support to form a stable three-core copper cluster structure to avoid nanoparticles agglomeration.
It has achieved high selective conversion of CO2 into high economic value C2 product ethanol, with weak hydrogen evolution side reaction and high CO2 conversion efficiency, which is suitable for large-scale industrial applications.
Smart Images

Figure CN119491260A_ABST
Abstract
Description
Technical Field
[0001] The present invention is directed to the field of green and sustainable electrocatalytic conversion, specifically a trinuclear copper cluster atomic-level catalyst for electrocatalytic carbon dioxide reduction. The material synthesis method in the present invention greatly reduces the generation of non-target metal nanoparticles and improves the controllability of atomic-level catalyst preparation. The trinuclear copper cluster atomic-level catalyst can achieve highly selective electrocatalytic reduction of CO2 molecules to C2 product ethanol with high economic value, and the hydrogen evolution side reaction is weak, and the overall CO2 conversion efficiency is high. Background Art
[0002] In addition to natural pathways such as carbon capture and storage through bioenergy, industrial technologies are also urgently needed to be developed and promoted to recycle redundant carbon emissions. In addition, the non-renewable nature of fossil fuels has led to the depletion of their underground storage resources, and solving the energy crisis has become an urgent matter. As an ideal solution, the electrocatalytic carbon dioxide reduction reaction can not only close the artificial carbon cycle, but also convert renewable energy such as solar energy and wind energy into chemical energy and store it in products with high added value, including clean fuels and industrial raw materials, thereby achieving a virtuous cycle of turning waste into treasure as a whole. In addition, the electrocatalytic carbon dioxide reduction also has many technical advantages, such as mild reaction conditions, which can be carried out at room temperature and pressure; the reaction is highly controllable, and the type, selectivity and conversion rate of the product can be adjusted by changing the applied potential and the alkalinity of the electrolyte; the reaction equipment is highly modular and suitable for large-scale industrial applications.
[0003] However, the C=O bonding barrier in the CO2 molecule is high, and its thermodynamic stability is high, which makes it difficult to activate. In addition, the complexity of the electrocatalytic carbon dioxide reduction reaction mechanism cannot be underestimated, and it includes a multi-step proton-coupled electron transfer process. So far, related research in the field of electrocatalytic carbon dioxide reduction is still in an emerging stage, and is far from mature compared with other electrochemical technologies such as water electrolysis for hydrogen production and fuel cells. The conversion products reported so far are mostly limited to C1 products such as CO, CH4, and HCOOH. In addition to the hydrogen evolution reaction as the main competing reaction, there is also a significant competitive relationship between different reduction products due to the close equilibrium potentials. Therefore, the development of stable catalysts with both high electrochemical activity and high selectivity for target products is a prerequisite for the practical application of electrocatalytic carbon dioxide reduction. It is worth mentioning that multi-carbon products with higher economic value are generally only generated on the surface of copper-based catalysts, making them the best choice for electrocatalytic carbon dioxide reduction catalysts. For example, the invention patent application with patent publication number CN118272859A applies for "a catalyst for electrocatalytic reduction of carbon dioxide to produce ethylene and its preparation method", which uses copper oxide nanoparticles as a substrate and doped with trace lanthanum elements to electrocatalytically reduce CO2 to C2 ethylene. However, liquid C2 products such as ethanol are more economically valuable and are more ideal reduction products. While retaining the advantages of single-atom catalysts such as easy adjustment of coordination structure and 100% atomic utilization, the three-atom catalyst has more flexibility in regulating the geometry and electronic structure of its metal active center, and the unique synergistic effect between multi-metal atoms enables it to break through the theoretical limit of the catalytic performance of single-atom materials. However, the synthetic controllability of multi-atom catalysts is poor, and it is very easy to agglomerate during the preparation process, thereby generating unfavorable nanoparticles. The invention patent application with patent publication number CN111659423B applies for "a method for preparing and using a cobalt-tellurium diatomic site catalyst". The main body is to use the confinement effect of ZIF-8 to make it act as a "cage" to encapsulate metal precursors to prevent the migration and aggregation of metal atoms during the subsequent thermal decomposition and removal of ligands. However, the preparation process of ZIF materials is cumbersome, and its packaging size is not completely compatible with any metal precursor, which indicates that the size between the "cage" and the precursor needs to be highly adapted, making the process show huge application limitations and difficult to large-scale industrial production. Therefore, the application of multi-atom catalysts in the field of electrocatalysis is still in its infancy, and is rarely used in electrocatalytic carbon dioxide reduction. Summary of the invention
[0004] Based on the current technical problems and application limitations of the synthesis of multi-atom materials, we designed a second-level pyrolysis imprinting technology to synthesize trinuclear copper cluster atomic-level catalysts. This technology not only has a simple preparation process, but also can effectively avoid the unfavorable atomic agglomeration phenomenon. And to a great extent, the coordination structure of the trinuclear copper atoms in the metal-organic precursor is retained, so that the synthesized trinuclear copper cluster catalyst has a high proportion of target triatomic groups. In addition, it also shows excellent electrocatalytic reduction of carbon dioxide, not only the hydrogen evolution side reaction is weak, but also can generate C2 product ethanol with high economic value with high Faraday efficiency, showing huge potential for large-scale industrial application. The specific technical scheme of the present invention is:
[0005] A trinuclear copper cluster atomic-level carbon dioxide reduction electrocatalyst: atomic-level copper ions and non-metallic nitrogen atoms are dispersed on a graphene-based carrier, and the copper ions are coordinated with carbon atoms and nitrogen atoms via stable valence bonds to form a special trinuclear copper cluster structure.
[0006] The copper content in the catalyst is 0.1-10.0 wt. %, and the nitrogen content is 0.1-20.0 wt. %.
[0007] The synthesis route of the above catalysts:
[0008] 1) Preparation of Cu3-NF precursor: Add 0.35 g CuCl2·2H2O to 50 mL deionized water, stir evenly to prepare solution A, add 0.15 g 1,2,4-triazole to 10 mL deionized water, stir evenly to prepare solution B, and mix solution A and solution B to precipitate powdery crystals (Cu3-NF).
[0009] 2) Weigh a certain amount of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar into the beaker, stir for 10 minutes, and ultrasonicate for 60 minutes to fully mix them into a uniform suspension;
[0010] 3) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0011] 4) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0012] 5) The Cu3-NF-GO material is placed in a fast-moving boat and under the protection of inert nitrogen, the temperature is ultra-fast increased at 700-200°C to achieve second-level calcination, and Cu3-NG is obtained after pyrolysis for 5 seconds.
[0013] In step 1), ensure the correct synthesis of the metal-organic complex Cu3-NF precursor.
[0014] In step 2), ensure that the Cu3-NF precursor and graphene oxide are dispersed in 80 mL of distilled water with high uniformity.
[0015] In step 2), a certain amount of Cu3-NF precursor and 100 mg of graphene oxide were weighed, and 2 mg, 6 mg, 12 mg, 18 mg or 25 mg of Cu3-NF precursor were weighed in parallel experiments to achieve the regulation of the copper atom loading of Cu3-NF-GO.
[0016] In step 3), ensure that the water in the suspension obtained in step 2) is completely removed by rotary evaporation.
[0017] In step 4), the black solid residue scraped from the rotary evaporator is ground in an agate mortar to obtain a black powder material (Cu3-NF-GO).
[0018] In step 5), the entire calcination process of the black Cu3-NF-GO powder must be carried out under the protection of inert nitrogen to avoid the formation of unfavorable oxides.
[0019] In step 5), the black Cu3-NF-GO powder needs to be ultra-fast heated to 1800°C with the assistance of a fast-moving boat, maintained for 5 seconds after the pyrolysis is completed, and then quickly cooled to room temperature in an inert atmosphere.
[0020] The present invention also provides application of the catalyst in electrocatalytic carbon dioxide reduction.
[0021] The beneficial effects of the present invention are:
[0022] The trinuclear copper cluster atomic-level catalyst synthesized by this method retains a high proportion of triatomic groups in the metal coordination structure of the precursor (Cu3-NF), and the ultrafast pyrolysis imprinting technology suppresses the formation of nanoparticles.
[0023] The heterogeneous and coordination effects between triatomic copper and the carbon-nitrogen carrier in the catalyst synthesized by this method can optimize the electronic state density between active copper sites, making them charge-rich centers that can adsorb and activate CO2 molecules.
[0024] The trinuclear copper cluster atomic catalyst synthesized by this method can achieve highly selective conversion of CO2 molecules into high value-added C2 product ethanol. The hydrogen evolution reaction is weak and the amount of by-product hydrogen generated is extremely low, achieving efficient electrocatalytic reduction of CO2 with a Faraday efficiency of nearly 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to make the application performance of the technical solutions or embodiments of the preparation method of the present invention clearer, the necessary drawings will be provided below for further explanation;
[0026] Figure 1 is the initial theoretical model of the catalyst of Example 1;
[0027] Figure 2 is a theoretical model of the adsorption of intermediates in the electrocatalytic carbon dioxide reduction reaction at the active copper sites in the catalyst of Example 1;
[0028] Figure 3 It is the X-ray diffraction pattern of Example 1 and Comparative Examples 1 and 2;
[0029] Figure 4 is the K-edge X-ray absorption near-edge structure spectra of Example 1 and Cu2O, CuPc and Cu foil;
[0030] Figure 5 is a transmission electron microscope image of Example 1;
[0031] Figure 6 is the spherical aberration corrected transmission electron microscope image of Example 1;
[0032] Figure 7 1 is the linear voltammetric curve of the electrocatalytic carbon dioxide reduction of Example 1 and Comparative Example 1;
[0033] Figure 8 The product generation and corresponding Faraday efficiency of Example 1, Comparative Examples 1, 2 and the leading copper-based carbon dioxide reduction electrocatalyst are compared; DETAILED DESCRIPTION
[0034] The synthesis technology and application purpose of the present invention are more clearly described in conjunction with the following examples. It is emphasized that the examples herein are only used to provide a more intuitive supplementary explanation of the present invention and are not limiting to the scope of the invention defined by the appended claims.
[0035] Example 1
[0036] 1) Preparation of Cu3-NF precursor: Add 0.35 g CuCl2·2H2O to 50 mL deionized water, stir evenly to prepare solution A, add 0.15 g 1,2,4-triazole to 10 mL deionized water, stir evenly to prepare solution B, and mix solution A and solution B to precipitate powdery crystals (Cu3-NF).
[0037] 2) Weigh 1.0 mg of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar to the beaker, stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0038] 3) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0039] 4) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0040] 5) Weigh 15 mg of Cu3-NF-GO material and place it in a fast-moving boat. Under the protection of inert nitrogen, ultra-fast heating is performed at 1800°C to achieve second-level calcination. After pyrolysis for 5 seconds, 1.0 wt% Cu3-NG (the optimized sample is abbreviated as Co3-NG) is obtained.
[0041] Example 2
[0042] 1) Weigh 20 mg of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar into the beaker and stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0043] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0044] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0045] 4) Weigh 15 mg of Cu3-NF-GO material and place it in a fast-moving boat. Under the protection of inert nitrogen, ultra-fast heating is performed at 1800°C to achieve second-level calcination. After pyrolysis for 5 seconds, 2.0 wt% Cu3-NG is obtained.
[0046] Example 3
[0047] 1) Weigh 50 mg of Cu3-NF precursor and 100 mg of graphene oxide into a 100 mL beaker, then add 80 mL of distilled water into the beaker, add a magnetic bar into the beaker, stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0048] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0049] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0050] 4) Weigh 15 mg of Cu3-NF-GO material and place it in a fast-moving boat. Under the protection of inert nitrogen, ultra-fast heating is performed at 1800°C to achieve second-level calcination. After pyrolysis for 5 seconds, 5.0 wt% Cu3-NG is obtained.
[0051] Example 4
[0052] 1) Weigh 70 mg of Cu3-NF precursor and 100 mg of graphene oxide into a 100 mL beaker, then add 80 mL of distilled water into the beaker, add a magnetic bar into the beaker, stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0053] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0054] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0055] 4) Weigh 15 mg of Cu3-NF-GO material and place it in a fast-moving boat. Under the protection of inert nitrogen, ultra-fast heating is performed at 1800°C to achieve second-level calcination. After pyrolysis for 5 seconds, 7.0 wt% Cu3-NG is obtained.
[0056] Example 5
[0057] 1) Weigh 100 mg of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar into the beaker and stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0058] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0059] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0060] 4) Weigh 15 mg of Cu3-NF-GO material and place it in a fast-moving boat. Under the protection of inert nitrogen, ultra-fast heating is performed at 1800°C to achieve second-level calcination. After pyrolysis for 5 seconds, 10.0 wt% Cu3-NG is obtained.
[0061] Comparative Example 1
[0062] 1) Weigh 12 mg of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar into the beaker and stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0063] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0064] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu3-NF-GO).
[0065] 4) Weigh 20 mg of Cu3-NF-GO material and place it in an ordinary porcelain boat in a tube furnace. Under the protection of inert nitrogen, heat the temperature to 750°C at a rate of 10°C per minute and maintain pyrolysis for 2 hours. Then cool it naturally to room temperature to obtain 2.0 wt% Cu3-NG-NP, which contains a large amount of nanoparticles formed by unfavorable agglomeration.
[0066] Comparative Example 2
[0067] 1) Weigh 20 mg CuCl2 and 100 mg graphene oxide and add them to a 100 mL beaker, then add 80 mL distilled water to the beaker, add a magnetic bar into the beaker and stir for 10 min, and ultrasonicate for 60 min to fully mix them into a uniform suspension;
[0068] 2) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension at a high vacuum condition of 75°C to remove the water solvent;
[0069] 3) Scrape all the black solid residue in the rotary evaporator and collect it in an agate mortar, and grind it thoroughly to obtain a black powder material (Cu-GO).
[0070] 4) Collect the black powder material Cu-GO in step 3) in an agate mortar, add melamine 3 times the volume of Cu-GO as a nitrogen source, and continue grinding until the two are evenly mixed to obtain an off-white powder (Cu-NF-GO).
[0071] 4) Weigh 15 mg of Cu-NF-GO material and place it in a fast-moving boat under the protection of inert nitrogen. Ultra-fast heating at 1800°C is achieved to achieve second-level calcination. After pyrolysis for 5 seconds, 2.0 wt% Cu-NG is obtained.
[0072] Structural testing:
[0073] Figure 1 Figure 2 The initial structure of the trinuclear copper cluster atomic-scale catalyst and the reaction structure applied to electrocatalytic carbon dioxide reduction are described.
[0074] Figure 3 The XRD results show that there is an obvious diffraction peak of Cu nanoparticles in Comparative Example 1, and there is no diffraction peak of Cu nanoparticles in Example 1 and Comparative Example 2, indicating that the ultrafast pyrolysis imprinting technology of the above samples effectively avoids adverse agglomeration during high-temperature calcination.
[0075] Figure 4 The XANES results of the Cu atomic K-edge show that, by comparison with the standard Cu2O, Cu foil and CuPC test spectra, the copper sites in Example 1 present an atomically dispersed tri-nuclear cluster distribution structure rather than existing in the form of nanoparticle oxides.
[0076] Figure 5 The high-resolution transmission electron microscope image shows that there are no Cu nanoparticles in the sample of Example 1.
[0077] Figure 6 The spherical aberration corrected transmission electron microscope image shows that Example 1 has multiple three copper atom groups distributed in a triangular shape, which are considered to be trinuclear copper atoms. This shows that this method effectively avoids the high-temperature agglomeration phenomenon and successfully synthesizes the trinuclear copper cluster atomic-level catalyst.
[0078] Performance testing:
[0079] In order to evaluate the catalytic activity of the samples of Comparative Examples 1, 2 and Examples 1, 2, 3, 4, and 5 for ECO2RR, we used a unified flow cell to evaluate the performance under the conditions of 20 ml / min 1M KOH electrolyte and 30 ml / min CO2 gas velocity driven by an electric peristaltic pump. The specific sample preparation steps are as follows: 2 mg of sample was mixed with 150 uL deionized water and 50 uL 1wt% Nafion solution and ultrasonicated for 60 min. The above-mentioned ultra-uniform ink was sprayed onto the gas diffusion layer of the cut 1.5 cm×1.5 cm carbon cloth using an electric spray gun. The sample loading was 1 mg / cm -2 The working electrode was obtained by drying the film at room temperature. In addition, calomel electrode and nickel foam were used as reference electrode and counter electrode respectively.
[0080] Figure 7The linear voltammetric curve shows that the ECO2RR activity of Example 1 is significantly better than that of Comparative Example 1, exhibiting a lower starting potential and a larger current density.
[0081] Figure 8 The comparison of the advantageous products of ECO2RR of different catalysts and their Faraday efficiencies shows that Example 1 can not only produce C2 product ethanol with high economic added value, but also has a higher Faraday efficiency of ethanol, indicating that Example 1 has more advantageous product types than Comparative Example 1, Comparative Example 2 and other copper-based catalysts, and exhibits more excellent conversion selectivity.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Therefore, any modifications made without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. Application of trinuclear copper cluster atomic-scale catalyst in electrocatalytic carbon dioxide reduction, characterized in that: Atomic copper ions and non-metallic nitrogen atoms are dispersed on a graphene-based carrier, and the copper ions are coordinated with carbon atoms and nitrogen atoms via stable valence bonds to form a special trinuclear copper cluster structure; The copper content in the catalyst is 0.1-10.0wt.%, and the nitrogen content is 0.1-20.0wt.%; The heterogeneous and coordination effects between triatomic copper and carbon-nitrogen carriers can optimize the electronic state density between active copper sites, making them charge-rich centers that can adsorb and activate CO2 molecules. The tri-nuclear copper cluster atomic catalyst can achieve highly selective conversion of CO2 molecules into high value-added C2 product ethanol, and the hydrogen evolution reaction is weak, and the amount of by-product hydrogen generated is extremely low, achieving a Faraday efficiency of more than 70% for efficient electrocatalytic reduction of CO2.
2. The use according to claim 1, characterized in that: The catalyst preparation steps are as follows: 1) Preparation of Cu3-NF precursor: Add 0.35 g of CuCl2·2H2O to 50 mL of deionized water and stir to prepare solution A; add 0.15 g of 1,2,4-triazole to 10 mL of deionized water and stir to prepare solution B; mix solution A and solution B to precipitate powdery crystals (Cu3-NF); 2) Weigh a certain amount of Cu3-NF precursor and 100 mg of graphene oxide and add them to a 100 mL beaker, then add 80 mL of distilled water to the beaker, add a magnetic bar into the beaker, stir for 10 minutes, and ultrasonicate for 60 minutes to fully mix them into a uniform suspension; 3) Transfer the suspension to a 250 mL rotary evaporator, and then use a rotary evaporator to spin dry the suspension under a high vacuum condition of 50-80°C to remove the water solvent; 4) Scrape all the black solid residues in the rotary evaporator and collect them in an agate mortar, and grind them thoroughly to obtain a black powder material (Cu3-NF-GO); 5) The Cu3-NF-GO material is placed in a fast-moving boat and under the protection of inert nitrogen, the temperature is ultra-fast increased at 700-2000°C to achieve second-level calcination, and Cu3-NG is obtained after pyrolysis for 5 seconds.
3. The use according to claim 2, characterized in that: In step 1), ensure the correct synthesis of the metal-organic complex Cu3-NF precursor.
4. The use according to claim 2, characterized in that: In step 2), ensure that the Cu3-NF precursor and graphene oxide are dispersed in distilled water with high uniformity.
5. The use according to claim 2, characterized in that: In step 2), a certain amount of Cu3-NF precursor and 100 mg of graphene oxide were weighed, and 2 mg, 6 mg, 12 mg, 18 mg or 25 mg of Cu3-NF precursor were weighed in parallel experiments to achieve the regulation of the copper atom loading of Cu3-NF-GO.
6. The use according to claim 2, characterized in that: In step 3), ensure that the water in the suspension obtained in step 2) is completely removed by rotary evaporation; in addition, in step 4), the black solid residue scraped from the rotary evaporator is fully ground in an agate mortar to obtain a black powder material (Cu3-NF-GO).
7. The use according to claim 2, characterized in that: In step 5), the entire calcination process of the black Cu3-NF-GO powder must be carried out under the protection of inert nitrogen to avoid the formation of unfavorable oxides.
8. The use according to claim 2, characterized in that: In step 5), the black Cu3-NF-GO powder needs to be ultra-fast heated to 700-2000°C with the assistance of a fast-moving boat, maintained for 5 seconds after the pyrolysis is completed, and then quickly cooled to room temperature in an inert atmosphere.
9. The use according to claim 1, characterized in that: In a gas diffusion flow electrolytic cell separated into a cathode tank and an anode tank by a proton exchange membrane, a calomel electrode and nickel foam are used as a reference electrode and a counter electrode respectively, and a carbon cloth coated with Cu3-NG in the gas diffusion layer is used as a working electrode to carry out constant current electrocatalysis of carbon dioxide to produce ethanol; an electric peristaltic pump is used to circulate cathode and anode electrolytes; The Cu3-NG was sprayed onto the gas diffusion layer of the carbon cloth by a spray gun to a loading amount of 0.1 to 5 mg cm -2 .
10. The use according to claim 1, characterized in that: The above balance current range is 50~2000mA cm -2 ; The electrolyte is potassium hydroxide with a concentration of 0.1 to 1.0 M, the electrolyte flow rate driven by the electric peristaltic pump is 10 to 100 ml / min; the carbon dioxide gas flow rate is 10 to 100 ml / min; The size of the carbon cloth with the gas diffusion layer is 1.0 cm×1.0 cm to 10.0 cm×10.0 cm.
Citation Information
Patent Citations
Preparation of carbon material covalent loading bionic multi-core copper-oxygen reduction electrocatalyst
CN104600329A
Preparation method and application of lamellar Cu-based N-doped graphene catalyst
CN114836781A
Light-emitting device and display device
CN118234278A
Nanocomposite Materials Comprising Metal-Organic-Framework Units and Graphite-Based Materials, and Methods of Using Same
US20110217217A1
Conductive or semi-conductive clusters produced via spark ablation
WO2024208806A1